Risk factors for recurrent Clostridium difficile infection in hematopoietic stem cell transplant recipients. Issue 5 (18th July 2014) - Huang, A.M.; Marini, B.L.; Frame, D.; Aronoff, D.M.; Nagel, J.L.
Abstract Background Recurrent Clostridium difficile infection (CDI) represents a significant burden on the healthcare system and is associated with poor outcomes in hematopoietic stem cell transplant (HSCT) patients. Data are limited evaluating recurrence rates and risk factors for recurrence in HSCT patients. Methods HSCT patients who developed CDI between January 2010 and December 2012 were divided into 2 groups: non‐recurrent CDI (nrCDI) and recurrent CDI (rCDI). Risk factors for rCDI were compared between groups. Rate of recurrence in HSCT patients was compared to that in other hospitalized patients. Results CDI was diagnosed in 95 of 711 HSCT patients (22 rCDI and 73 nrCDI). Recurrence rates were similar in HSCT patients compared with other hospitalized patients (23.2% vs. 22.9%, P > 0.99). Patients in the rCDI group developed the index case of CDI significantly earlier than the nrCDI group (3.5 days vs. 7.0 days after transplant, P = 0.05). On univariate analysis, patients with rCDI were more likely to have prior history of CDI and neutropenia at the time of the index CDI case. Neutropenia at the time of the index CDI case was the only independent predictor of rCDI (78.8 vs. 34.8%, P = 0.006) on multivariate analysis. Conclusions The rate of rCDI was similar between HSCT and other hospitalized patients, and the majority of patients developed the index case of CDI within a week of transplantation. Neutropenia at the index CDI case may be associated with increased rates of rCDI.